Property valuation under uncertainty. Simulation vs strategic model - Meszek, Wiesław (International Journal of Strategic Property Management, 2013)
Uncertainty is a real and universal phenomenon in property valuation. The sources of uncertainty premises originate in the market’s specific character, particularly in its informative inefficiency. The degree of uncertainty will vary according to the level of market activity. The result of this uncertainty for the process of property valuation is the impossibility of the measurement of the market value weights and unknown reliability of the real estate transaction prices. In practice, the market value of each property is based on prices under the assumption that the market is efficient; however in reality, prices do not fully reflect the available information. The reasons are, among others, low transparency of the market and confidentiality of transactions let alone the market imperfections. In terms of information inefficiency of the real estate market, statistical methods are ineffective for property valuation, therefore there is a need to use methods and models taking uncertainty into consideration. This paper looks at the way in which uncertainty can be incorporated into the explicit model of sales comparison approach (pairwise comparison method). One model focuses on the application of the Monte-Carlo simulation and the other on the game theory. First Publish Online: 3 Apr 2013